2019
DOI: 10.1039/c8ra09454c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the surface plasmon resonance in gold nanocrystals with single layer carbon nitride

Abstract: Interaction of forming Au nanocrystals with single-layer carbon nitride nanosheets allows the surface plasmon resonance peak position of gold/carbon nitride composites to be tuned in a range of 520–610 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Significant research efforts have been devoted to the synthesis of Au nanocrystals of different size and size distribution to tailor the SPR absorption band (peak position, shape and intensity), Yet, Stroyuk and co‐workers lately argued, this approach led only to modest changes in the position of SPR band maximum over a broad range of Au nanocrystal size and shape (a red shift of the SPR maximum of 50–65 nm when going from 5–10 nm to 100–110 nm nanoparticles).…”
Section: Tuning the Surface Plasmon Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…Significant research efforts have been devoted to the synthesis of Au nanocrystals of different size and size distribution to tailor the SPR absorption band (peak position, shape and intensity), Yet, Stroyuk and co‐workers lately argued, this approach led only to modest changes in the position of SPR band maximum over a broad range of Au nanocrystal size and shape (a red shift of the SPR maximum of 50–65 nm when going from 5–10 nm to 100–110 nm nanoparticles).…”
Section: Tuning the Surface Plasmon Resonancementioning
confidence: 99%
“…The approach has been recently demonstrated by Stroyuk and co‐workers using single layer carbon nitride (SLCN) nanosheets added at the stage of the formation of Au nanocrystals . Now, the key parameters of the SPR (absorption peak position, band shape and intensity) are tuned by chemical functionalization of the Au nanocrystals expanding control on the SPR and nonlinear optical (NLO) properties well beyond the “modest” changes observed when tuning the shape and size of the Au nanocrystals.…”
Section: Tuning the Surface Plasmon Resonancementioning
confidence: 99%
“…Recently, Cheng et al reported graphite carbon nitride nanosheet containing AgPd bimetallic nanoparticles with Ag plasmonic effect as an effective Mott-Schottky photocatalyst to catalyzing the evolution of H 2 from the formic acid under visible light 42 . Compared to bulk g-C 3 N 4 , the single layer carbon nitride is an emerging photocatalyst with a layered structure due to its unique properties such as photogenerated charge carrier lifetime, specific surface area, shorter bulk diffusion length, and high carrier density reduces the possibility of recombination of charge carriers and affords more surface-active sites for metal stabilization 60 63 . Inspired by the aforesaid considerations and in line with our recent efforts in the field of clean energy and hydrogen production 28 , 64 69 , here we offer the synthesis of bimetallic AgPd NPs decorated on single layer carbon nitride (SLCN) as an active plasmonic photocatalyst for the evolution of H 2 from FA.…”
Section: Introductionmentioning
confidence: 99%
“…1 The applications of LSPR include surface-enhanced Raman scattering (SERS), [2][3][4][5][6][7] plasmon-enhanced photoluminescence, [8][9][10][11][12] and related optical sensing techniques, 9,[13][14][15][16][17][18][19] bio-imaging, 20 photothermal approaches in anti-tumor therapy, 21,22 plasmonenhanced energy-harvesting, 23 etc. Numerous methods of synthesis of colloidal NPs have been developed so far, 1,2,14, [24][25][26][27] with the facile methods of producing bio-compatible NPs being one of the main research focuses in the community. [28][29][30] Among the most oen used syntheses is the one leading to a colloidal system of spherical gold NPs based on a simple reaction reducing auric acid with either sodium citrate or sodium borohydride.…”
Section: Introductionmentioning
confidence: 99%